FACTORS RELATED TO KNOWLEDGE ON NEWBORN DANGER SIGNS AMONG THE RECENTLY DELIVERED WOMEN IN SUB-DISTRICT HOSPITALS OF BANGLADESH - Zaman, Sojib Bin; Hossain, Naznin; Hussain, Muhammed Awlad; Abimanue, Vidhuna; Jahan, Nushrat; Zaman, Rafid Bin; Ratan, Zubair Ahmed; Khan, Raihan Kabir; Sharmin, Shuchita (Public Health of Indonesia, 2017)
Background: Bangladesh continues to be one of the top ten countries with the highest burden of neonatal mortality. While, most of the neonatal deaths are preventable; health system delays, delayed identification of newborn danger signs, late diagnosis and initiation of treatment are claimed to be the main challenges.Objective: 1) to determine the level of knowledge among the recently delivered women (RDW) about newborn danger signs and 2) to distinguish the factors associated with ability of identifying the danger signs.Methods: A facility based cross-sectional study was conducted in three sub-district hospitals of Bangladesh among 135 RDW between 1 January 2015 and 30 April 2015. Seven key danger signs were identified, and responses were categorized accordingly. Bivariable logistic regression was conducted to determine the likelihood of the association of factors with danger signs identification.Results: About 51% of RDW could identify one key danger sign. Knowledge on "fever'' was the most commonly known danger sign (65%). Middle age (OR 1.67, 95% CI: 1.09 - 2.18), high education (OR 2.37, 95% CI: 1.46 - 2.77), increased parity (OR 1.91, 95% CI: 1.17 - 2.89), and previous hospital delivery (OR 1.79, 95% CI: 1.14 - 2.68) were found associated with the knowledge of the danger signs.Conclusion: The findings indicate the immediate need to enhance health education among the RDW about newborn danger signs before their hospital discharge. Community based health education programs can be a cost effective intervention to increase awareness and early recognition of neonatal danger signs.